HUBUNGAN ANTARA DUKUNGAN SOSIAL GURU DENGAN KEMAMPUAN SOSIALISASI PADA ANAK RETARDASI MENTAL DI SLB PUTRA MANUNGGAL GOMBONG KEBUMEN - Risnawati, Desi Dwi; ummah, Basirun al; Septiwi, Cahyu (LPPM STIKES MUHAMMADIYAH GOMBONG, 2010)
Mental Retardation Children really need teacher’s social support. Social support is information from the society that shows that they are loved and noticed. They have self-respect and worth. It is a part of communication and liabilities. Mental Retardation is the situation where a common intellectual function lies subnormal and the beginning of individual development that engages learning ability and adaptation energy in individual maturation process. The aim of this study is to identify a correlation between teachers social support and socialization ability of mental retardation’s children at SLB Putra Manunggal Gombong, Kebumen Correlation descriptive research by using Cross Sectional approach. The research samples that consisted of 10 students (n = 10) of elementary school that experienced mental retardation and study in SLB Putra Manunggal Gombong. The Independent variable was teacher’s social support. The dependent variable was the socialization ability of mental retardation children. The statistical analysis used was Kendal Tau statistical test. Based on the Kendal Tau correlation statistical test, it was found that coefficient correlation between social support teachers and mental retardation’s children socialization was about 0,560 with probability value (Sig) 0,041< 0,05. There is a significant correlation between teachers social support and socialization ability of mental retardation’s children at SLB Putra Manunggal Gombong, Kebumen Keywords : Social Support, Socialization Ability, Mental Retardation Children.